Burnout among Portuguese radiographers during the COVID-19 pandemic. Issue 4 (November 2021) - Pereira, J.M.; Silva, C.; Freitas, D.; Salgado, A.
Abstract: Introduction: The COVID-19 pandemic has had a global impact, including in health services, placing health professionals under enormous tension, pressure, and stress. Professionals involved in the care, diagnosis, and treatment of COVID-19-infected patients have been subject to emotional and physical distress that can potentially enhance the development of occupational diseases. The aim of this study was to assess the impact of the COVID-19 pandemic on the incidence of burnout among Portuguese radiographers. Methods: This was a cross-sectional, quantitative study. Burnout levels were estimated using the Maslach Burnout Inventory-Human Services Survey, composed of 22 questions. Specific questions were developed to characterize the socio-demographic situation and the impact of the pandemic on the radiographers. Data were descriptively analyzed and Mann–Whitney and Kruskal–Wallis tests were used for correlation analysis. Results: The study sample comprised 386 radiographers, 68.7% of whom where female and 31.3% male. The mean sample age was 36.3 (±9.1) years. A total of 43.5% and 45.5% of subjects had a high level of emotional exhaustion and depersonalization, respectively, and 59.8% experienced low personal accomplishment. Altogether, 23.3% of study participants were at high risk of burnout in the three dimensions assessed and 77.2% in at least one. Conclusion: Study results showed that radiographers were at high risk of developing burnout in the COVID-19 pandemic setting. Health institutions should actively monitor these professional's mental health and develop restorative strategies that enable their emotional wellbeing, preventing absenteeism and increasing patients' quality of care. Implications for practice: Burnout of health professionals has a strong impact on health services organization, resulting in increased absenteeism and error probability, frequent work delays, low productivity and job satisfaction, inter- and intra-professional conflicts, high job turnover, high job quit, and decreased quality of care perceived by users.